Prognostic value of temporalis muscle thickness as a marker of sarcopenia in intracerebral hemorrhage - Gubarev, Waldemar; Klinke, Jan; Voßmann, Ulrike; Cantré, Daniel; Zendeh Zartoshti, Bijan; Rafaelian, Artem; Arsenovic, Milos; Dubinski, Daniel; Won, Sae-Yeon; Gessler, Florian; Freiman, Thomas; Storch, Alexander; et al. (Frontiers in Neurology, 2025)
IntroductionEstimating the prognosis of spontaneous intracerebral hemorrhage (ICH) is of great importance. It has not been conclusively clarified whether sarcopenia is predictive for the functional outcome in ICH. Determining the temporalis muscle thickness (TMT) may be helpful for estimating sarcopenia. An association of TMT with outcome (mRS) has been shown in cerebellar ischemia and traumatic brain injury.MethodsThe present retrospective study of 488 consecutive patients with ICH aimed to investigate the association of sarcopenia as assessed by TMT with mRS. In addition to biometric data, ICH subtype and severity [modified ICH score (mICH)], occurrence of complications and mRS at discharge and after 90 days were recorded. The influence of sarcopenia assessed by TMT as the surrogate marker using head imaging (cCT, cMRT) on mRS was analyzed by ordinal regression analysis. Dichotomization into sarcopenic and non-sarcopenic patients was carried out using standard threshold values.ResultsFinally, 322 patients were analyzed [median (IQR) age: 77 (66–83) years; 57.5% male]. Sarcopenic patients were older (P < 0.001), had lower BMI (P = 0.025) and higher mICH scores (P < 0.001) compared to non-sarcopenic patients. There was no significant difference in the overall distribution of mRS scores between sarcopenic and non-sarcopenic patients at discharge (unadjusted common OR: 1.28; 95% CI: 0.85–1.92; P = 0.236), but at 90 days favoring the non-sarcopenic over the sarcopenic group (unadjusted common OR: 1.41; 95% CI: 1.07–2.12; P = 0.049). The results did not subsist statistical adjustment to candidate covariates by multivariate ordinal regression.DiscussionIn conclusion, sarcopenia as assessed by TMT seems to have limited prognostic value in ICH.